The PHF21A neurodevelopmental disorder: an evaluation of clinical data from 13 patients. Issue 2 (21st April 2023) - Poole, Rebecca L.; Bijlsma, Emilia K.; Houge, Gunnar; Jones, Gabriela; Mikštienė, Violeta; Preikšaitienė, Eglė; Thompson, Louise; Tatton-Brown, Katrina
Abstract : Potocki–Shaffer syndrome (PSS) is a rare neurodevelopmental disorder caused by deletions involving the 11p11.2-p12 region, encompassing the plant homeodomain finger protein 21A ( PHF21A ) gene. PHF21A has an important role in epigenetic regulation and PHF21A variants have previously been associated with a specific disorder that, whilst sharing some features of PSS, has notable differences. This study aims to expand the phenotype, particularly in relation to overgrowth, associated with PHF21A variants. Analysis of phenotypic data was undertaken on 13 individuals with PHF21A constitutional variants including four individuals described in the current series. Of those individuals where data were recorded, postnatal overgrowth was reported in 5/6 (83%). In addition, all had both an intellectual disability and behavioural issues. Frequent associations included postnatal hypotonia (7/11, 64%); and at least one afebrile seizure episode (6/12, 50%). Although a recognizable facial gestalt was not associated, subtle dysmorphic features were shared amongst some individuals and included a tall broad forehead, broad nasal tip, anteverted nares and full cheeks. We provide further insight into the emerging neurodevelopmental syndrome associated with PHF21A disruption. We present some evidence that PHF21A might be considered a new member of the overgrowth-intellectual disability syndrome (OGID) family.